Malonyl-Coenzyme A Reductase from Chloroflexus aurantiacus, a Key Enzyme of the 3-Hydroxypropionate Cycle for Autotrophic CO(2) Fixation - Hügler, Michael (American Society for Microbiology, 2002)
The 3-hydroxypropionate cycle is a new autotrophic CO(2) fixation pathway in Chloroflexus aurantiacus and some archaebacteria. The initial step is acetyl-coenzyme A (CoA) carboxylation to malonyl-CoA by acetyl-CoA carboxylase, followed by NADPH-dependent reduction of malonyl-CoA to 3-hydroxypropionate. This reduction step was studied in Chloroflexus aurantiacus. A new enzyme was purified, malonyl-CoA reductase, which catalyzed the two-step reduction malonyl-CoA + NADPH + H(+) → malonate semialdehyde + NADP(+) + CoA and malonate semialdehyde + NADPH + H(+) → 3-hydroxypropionate + NADP(+). The bifunctional enzyme (aldehyde dehydrogenase and alcohol dehydrogenase) had a native molecular mass of 300 kDa and consisted of a single large subunit of 145 kDa, suggesting an α(2) composition. The N-terminal amino acid sequence was determined, and the incomplete gene was identified in the genome database. Obviously, the enzyme consists of an N-terminal short-chain alcohol dehydrogenase domain and a C-terminal aldehyde dehydrogenase domain. No indication of the presence of a prosthetic group was obtained; Mg(2+) and Fe(2+) stimulated and EDTA inhibited activity. The enzyme was highly specific for its substrates, with apparent K(m) values of 30 μM malonyl-CoA and 25 μM NADPH and a turnover number of 25 s(−1) subunit(−1). The specific activity in autotrophically grown cells was 0.08 μmol of malonyl-CoA reduced min(−1) (mg of protein)(−1), compared to 0.03 μmol min(−1) (mg of protein)(−1) in heterotrophically grown cells, indicating downregulation under heterotrophic conditions. Malonyl-CoA reductase is not required in any other known pathway and therefore can be taken as a characteristic enzyme of the 3-hydroxypropionate cycle. Furthermore, the enzyme may be useful for production of 3-hydroxypropionate and for a coupled spectrophotometric assay for activity screening of acetyl-CoA carboxylase, a target enzyme of potent herbicides.